Implementation of Total Quality Management (TQM) on Teaching Factory (TEFA) Vocational Middle School in Bogor District - Tjipto Djuhartono; Prasetio Ariwibowo; Lubban Anwari Alhamidi (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
The purpose of this qualitative research was to determine and analyze the effectiveness of the implementation of the Total Quality Management (TQM) program in Vocational High Schools in Bogor Regency and to determine and analyze the effectiveness of the implementation of Total Quality Management (TQM) on Teaching Factory (TEFA) in Vocational High Schools in the District. Bogor. The research location was conducted at SMK Negeri 01 Bogor Regency and SMKS PGRI Citeureup based on purposive sampling and library research from statistical data at the Bogor Regency Education Office and the Bogor Regency Ministry of Religion as the primary and secondary data objects for analysis. Data collection techniques using interview techniques, observation or observation, and documentation studies with data analysis techniques using data reduction, data presentation, and drawing conclusions or verification. The results of this study are The process of implementing TQM teaching factory in learning at SMK PGRI 01 Cibinong and SMKS PGRI Citeureup refers to the concept of Plan - Do - Check - Action (PDC). The plan (input) includes planning learning tools such as curriculum implementation, syllabus, lesson plans, attendance, teaching materials, media, assessment sheets and worksheets. Do (Process) includes carrying out learning according to planned lesson plans and the teaching factory learning model and block system. Output (Control) includes the implementation of learning evaluation, competency evaluation, teacher performance evaluation and internal audit, and making improvements and adjustments according to the assessment from the industry on an ongoing basis.